A Systematic Literature Review of Challenges and Critical Success Factors in Agile Requirement Engineering - Saleh, Mohammed; Baharom, Fauziah; Mohamed, Shafinah Farvin Packeer; Ahmad, Mazida (2018)
Nowadays, the complexity of software requirement has been increased due to the rapidly changing requirements. Therefore, Agile software development has been widely adopted as it promises some benefits such as continuous changes and customer satisfaction to handle the increase of complexity. However, agile requirement engineering is still facing some challenges and limitations, hence the process has been widely explored by the academicians and researchers. Hence, this paper aims to investigate and understand the concepts of agile requirement engineering by using Systematic Literature Review (SLR). Initially, 2530 articles were obtained through search without restrictions. Then, the total number of articles was reduced to 145 articles which published from 2002 until March 2018. After analyzing the articles, the paper presents ten (10) challenges, seven (7) critical success factors and four (4) issues of agile requirements engineering that need more attention by the researchers in the future studies